UPAYA HUKUM PENANGGULANGAN KEKERASAN DALAM RUMAH TANGGA (STUDI : PENGADILAN NEGERI GIANYAR) - I Kadek Dwipayana; I Wayan Suardana; I Gusti Ngurah Parwata (Kertha Negara : Journal Ilmu Hukum, 2013)
Domestic violence has been a distinctive discourse in everyday life. Women and children as the main victims of domestic violence, it requires absolute protection. Generally people believe that home and family is a safe place, a refuge from the danger outside the home, a place to share the warmth and love. But in fact a lot of a crime happen at home, within the family. next can be formulated about whether the efforts conducted by the Government of Gianyar regency in overcoming domestic violence cases and How to Sanctions of Law To The Domestic Violence. This writing use empiric juridical method to discuss the issue. Last it can be concluded that the efforts of the Government of Gianyar regency is making the policy or programs and preventive move by giving knowledge or category as well as the prohibitions contrary to the Law No. 23 of 2004 and for Sanctions Law To The Domestic Violence actors previously regulated in Law no. 7, 1984 on the Ratification of the Convention on All Forms of Discrimination To The Women and then updated by Law No. 23 of 2004 on the Elimination of Domestic Violence which is expected accommodative prevent the occurrence of domestic violence.